The Effect of Transfer Pricing, Capital Intensity, and Institutional Ownership on Tax Avoidance Moderated By Executive Characteristics in Food and Beverage Companies in 2020 - 2023 - Charlie Thyawarta; Ngadiman (Journal Research of Social Science, Economics, and Management, 2025)
Tax avoidance remains a critical challenge in Indonesia’s food and beverage sector, causing significant revenue losses and undermining public trust. Despite regulatory reforms like the Harmonization of Tax Regulations Law, corporate tax avoidance strategies such as transfer pricing, capital intensity manipulation, and institutional ownership dynamics persist, often influenced by the characteristics of company executives. This study aims to investigate the direct effects of transfer pricing, capital intensity, and institutional ownership on tax avoidance, and examine the moderating role of executive characteristics on these relationships. Employing a quantitative approach with panel data regression analysis, this research analyzes secondary financial data from food and beverage companies listed on the Indonesia Stock Exchange from 2020 to 2023. The results indicate that capital intensity has a significant positive effect on tax avoidance, while transfer pricing and institutional ownership do not directly influence tax avoidance. Executive characteristics moderate the relationships between transfer pricing and tax avoidance, as well as institutional ownership and tax avoidance, but do not moderate the effect of capital intensity. These findings highlight the complex role of leadership traits in shaping tax behavior and suggest that policy efforts should consider executive profiles alongside financial strategies. Future research should explore additional moderating variables and extend analyses to other sectors and regions to improve tax compliance frameworks.